Biopromoters for Gas Hydrate Formation: A Mini Review of Current Status - Zhang, Yong-Tao; Chen, Fu-Lin; Yu, Shi-Jie; Wang, Fei (Frontiers in Chemistry, 2020)
Gas hydrates have promising application prospects in the fields of future energy sources, natural gas storage and transportation, CO2 capture and sequestration, gas separation, and cold energy. However, the application of hydrate technologies is being restricted due to the slow formation rate of gas hydrates. Kinetic promoters have been receiving increased attention, given that they can improve the hydrate formation rate with very small doses and do not affect gas storage capacity. However, most kinetic promoters are non-renewable, petrochemical-derived, non-degradable materials, inevitably leading to resource waste and environmental pollution. Biopromoters, derived from biomass, are renewable, biodegradable, environmentally friendly, non-toxic (or low toxic), and economically feasible. This mini review summarizes the current status of already discovered biopromoters, including lignosulfonate, amino acid, biosurfactant, and biological porous structures, which have the potential to replace petrochemical-derived promoters in hydrate technologies. Finally, future research directions are given for the development of biopromoters.